Medically unexplained physical symptoms in patients visiting the emergency department: an international multicentre retrospective study. (August 2019) - Alsma, Jelmer; Wouw, Jens van de; Jellema, Korné; Coffeng, Sophie M.; Tobback, Els; Delesie, Liesbeth; Brand, Crispijn L. van den; Vogelaers, Dirk; Mariman, An; Paepe, Peter de; van Saase, Jan L.; Weiland, Anne
Abstract : Objective: The objective of this study was to assess the incidence and characteristics of patients presenting with physical symptoms that remain medically unexplained at the emergency department (ED). Patients and methods: A retrospective chart study was carried out in three hospitals in The Netherlands and Belgium. All patients (age > 18 years) visiting the ED in 4 selected weeks in 2013 at the Erasmus University Medical Center (Erasmus MC) in Rotterdam, The Netherlands, and 1 selected week in 2013 at the Haaglanden Medical Center, Westeinde HMC in The Hague, The Netherlands, and the University Hospital Ghent (UZG), Belgium, were included. Descriptive statistics were used for data analysis. Results: A total of 2869 patients (Erasmus MC 1674, HMC 691, UZG 504) were included. Medically unexplained physical symptoms in the emergency department (EDMUPS) were present in 13.4% of all ED visits (Erasmus MC 12.5%, HMC 18.7%, UZG 9.1%). No EDMUPS were identified in trauma patients. When excluding trauma patients, EDMUPS were present in 18.5% (Erasmus MC 16.8%, HMC 26.5%, UZG 13.3%) of the visits. The characteristics of patients with and without EDMUPS differed significantly; patients with EDMUPS were more often younger, female, self-referred, frequent visitors, were prescribed less medication and more often had a psychiatric disease. Dutch and Belgian Hospital differed in the distribution of patients in triage categories and in the incidence of psychiatric illnesses. Conclusion: Physical symptoms remain unexplained in a significant number of patients at the time of ED assessment.